2006 IEEE 17th International Symposium on Personal, Indoor and Mobile Radio Communications 2006
DOI: 10.1109/pimrc.2006.254256
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Soft Handover Micro Diversity Gain on the UMTS System Capacity and QoS

Abstract: In this paper the impact of the soft handover micro diversity gain on the UMTS system performance is investigated. First, by means of link layer simulations the micro diversity gain is measured in terms of reduction of the average E b /N 0 requirement. After modelling this effect, by some system level simulations we show the high influence of this usually neglected gain in the overall performance of UMTS, demonstrating that in downlink soft handover improves not only the quality of service but also the overall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2009
2009
2011
2011

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…The 3-way SHO has a slight improvement(0.2dB) in comparison w Figure 8 illustrates the BER versus average SNR for no SHO, 2-way SHO, and 3-way SHO. From [13] the required BER for voice service is 10 -3 , to obtain this value, the required SNR without SHO is 24dB, while with 2-way SHO is 12.1dB, and with 3-way SHO is 7dB. It can be concluded that SHO decreases the average SNR by approximately 50% and 70% for 2-way SHO and 3-way SHO respectively when BER=10 -3 .…”
Section: Resultsmentioning
confidence: 92%
See 3 more Smart Citations
“…The 3-way SHO has a slight improvement(0.2dB) in comparison w Figure 8 illustrates the BER versus average SNR for no SHO, 2-way SHO, and 3-way SHO. From [13] the required BER for voice service is 10 -3 , to obtain this value, the required SNR without SHO is 24dB, while with 2-way SHO is 12.1dB, and with 3-way SHO is 7dB. It can be concluded that SHO decreases the average SNR by approximately 50% and 70% for 2-way SHO and 3-way SHO respectively when BER=10 -3 .…”
Section: Resultsmentioning
confidence: 92%
“…Substituting (13) into (6) and (11), the actual transmit power under imperfect power control situation with 2-way SHO and 3-way SHO respectively can be obtained as [12]:…”
Section: From Equation 3 (E B /I O ) 1 and (E B /I O ) 2 Can Be Founmentioning
confidence: 99%
See 2 more Smart Citations
“…Downlink soft handoff performance in WCDMA was studied in [8] and the results led to that 2-way soft handoff reduces the required dedicated transmission power up to 3dB, moreover, soft handoff gain has better value at soft handoff overhead equal to 30% . In [9] the impact of soft handoff on the UMTS system performance is investigated, and the results approved that in downlink, soft handoff improves not only the quality of service but also the overall system capacity.…”
Section: Introductionmentioning
confidence: 96%